Biomass and growth rates behavior of two varieties of Iulo (Solanum qurtoense Lam.) in Pachavita—Boyaca - Almanza-Merchán, Pedro José; Tovar-León, Yeily Paola; Velandia-Díaz, Julián David (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The two fruit varieties growth and development dynamics of lulo (Chonto grueso and Criollo) was studied under conditions of Pachavita municipality, of Boyacé department. Dry biomass, the Absolute Growth Rates (AGR) and Relative Growth (RGR) were evaluated. The two fruits varieties have a simple sigmoid growth, with three phases which were described as: FI (cell division), FII (cell elongation) and FIII (maturation). The Chonto grueso variety showed an exponential increase in the AGR covering the FI and part of the FII, up to 78 days after anthesis (DAA) when it reached its highest value of 0.117 g/day, and a rapid dw mass gain, up to this point, then decreased until harvest. The Criollo variety showed a slow increase in the FI, which was progressive until reaching its peak at 128 DAA, accumulating 0.107 g/day, which meant a slower increase in size over time, demonstrating greater initial landfill power in Chonto grueso variety, regarding the Criollo variety in terms of dry matter. The RGR for Chonto grueso variety showed a slow decline in FI, drastically reduced in FII and slowly in the FIII; while the Criollo variety showed a gradual and steady decline to 140 DAA. It was established for the Chonto grueso variety in FIII and in general for the Criollo variety, a low rate of change in size per unit initial size.